Maradona, accanito tifoso del pugilato - Palla, Jonathan (Eracle. Journal of Sport and Social Sciences, 2022)
Ubaldo Sacco and Martín Látigo Coggi, were boxers who received the support and public admiration of Maradona in Italy, when they faced the Neapolitan Patrizio Oliva, during the 1980s, especially when the footballer became the hero of the Neapolitan fans. This work investigates the performative accounts of a part of the Italian and Argentine press, the repertoire of images in which those sports battles were narrated, as well as the points of view of the actors involved, tracing the articulation and superposition of a range of identifications of local, national and international belongings.